Two water wells of the LBK culture from the north part of the site of Kruszyn 3/10, Włocławek commune - Rzepecki, Seweryn (Fundacja Rzeszowskiego Ośrodka Archeologicznego, 2014)
The aim of the present paper is to present two water wells from a settlement of the LBK culture at the site of Kruszyn 3/10, Włocławek commune. The features under consideration are dated to phase IIB of this culture in Kuyavia. They represent the simplest, timberless types of devices which were used to supply water. The author also pays attention to non-utalitarian aspects connected with cult and ritual meaning of water wells in the LBK societies.
Dwie studnie kultury ceramiki wstęgowej rytej z północnej części stanowiska Kruszyn 3/10, gm. Włocławek
Keywords: LBK culture; water wells; Kuyavia; Kruszyn 3/10